Рrospects of health and medical tourism clusterization in Ukraine - Mariia Bieloborodova (Вісник Харківського національного університету імені В.Н. Каразіна: Серія Міжнародні відносини, економіка, країнознавство, туризм)
Ukrainian health and medical tourism needs a change in strategic planning approaches due, firstly, to the outdated post-Soviet organization of mass rehabilitation and sanatorium-resort treatment, and, secondly, in connection with the expected changes in the structure of consumers and their advantages, both as a result of the full-scale invasion of the russian federation. The subject of the study is the clustering processes in the field of health and medical tourism of Ukraine. The purpose of the study is to substantiate the methodical approach to the clustering of health and medical tourism based on spatial modeling of the relevant resource and material base. The task of the research: substantiating the main directions of health and medical tourism development; generalization of statistical data on the resource and material base based on the method of cartographic visualization; development of proposals for the activation of cluster processes based on statistical groupings of regions. The following methods were used: abstract (theoretical generalizations, formulation of conclusions), systematic approach, method of structural generalization, statistical grouping, graphic method. The following results were obtained: on the basis of statistical analysis, it was proposed to divide the regions of Ukraine into the following groups: the first - seaside regions,  specialization – family and children's recreational and health tourism; the second – Volyn and Carpathian region, specialization - sanatorium-resort and rehabilitation vacation with an emphasis on inbound tourism; the third – capital and central-eastern regions, specialization – medical tourism; the fourth – regions without a pronounced potential for health and medical tourism, in total make up 46.47% of the area. The stages for the clustering policy implementation of health and medical tourism in Ukraine have been developed. Conclusions: to improve the management of health and medical tourism, a clustering tool is proposed. The regions of Ukraine are divided into four groups according to the level of resource and material base development, each of which has a clear specialization and target tourist groups, as well as the direction of strategic development. This improves the strategic promotion of domestic health and medical tourist destinations at the inbound and outbound directions.